UV-induction of keratinocyte endothelin-1 downregulates E-cadherin in melanocytes and melanoma cells - Jamal, Sumayah (American Society for Clinical Investigation, 2002)
Endothelin-1 (ET-1), a peptide that is secreted by keratinocytes in the skin in response to ultraviolet irradiation, is a ligand for the endothelin-B (ET(B)) receptor. Blockade of this receptor inhibits melanoma cell growth and induces cell death in vivo and in vitro. Additionally, ET(B) is a melanoma progression marker. These findings suggest that the ET-1/ET(B) receptor pathway contributes to melanoma development or progression. Here, we demonstrate that activation of the ET-1/ET(B) pathway downregulates E-cadherin and associated catenin proteins in human melanocytes and melanoma cells. E-cadherin is an established suppressor of melanoma cell invasion in vitro and in vivo. Downregulation of E-cadherin by ET-1/ET(B) involves the downstream activation of caspase-8 but not of distal, executioner caspases, and does not lead to apoptosis. ET-1 also induces a transient association between caspase-8 and E-cadherin:β-catenin complexes. Hence, activation of the ET-1/ET(B) pathway promotes molecular events known to promote melanoma invasion.